Investigation of industrial herding in Malaysia - Mohd Nasarudin, Ahmad Fawwaz (2018)
This paper examines herding behavior in Malaysia using their industrial daily price data for the period of 2005-2018. The study report insignificant results when test for the whole period using the Cross Sectional Absolute Deviation (CSAD). However, the study document significant herding activity in the second test across the year particularly in the earlier years between 2005 and 2011. Similar test on the succeeding years however did not report for any herding activity except for 2015. Beside the heighten apprehension during crisis time, this could also due to the rapidly advancing technology enabling investors to obtain information and make decision heterogeneously. Meanwhile, study on herding across industrial in Malaysian market shows that only technological and property sectors give significant herding activity pointing to an improve efficient market in the country